Students’ Strategies to Overcome Anxiety in Speaking English at The Second Grade Students Of SMK Negeri 6 MBD - Tetrapoik, Dominggas; Lekawael, Rosina F. J.; Tiwery, Dian S. (Koli Journal : English Language Education, 2022)
This study aimed to (a) find out kinds of the Students Strategies used to overcome their anxiety in speaking English; and (b) find out the factors that influence students’ anxiety in speaking English. The data was collected from second-grade students at SMK Negeri 6 Maluku Barat Daya as the subject. This study used a mixed method. The instruments used were interviews and questionnaires. The interview was distributed to 6 students based on students' grades, for the highest, the middle, and the lowest two students consisting of the Department of Agriculture, livestock, and Fisheries. The questionnaire was adapted from Horwitz and Cope’s (1986) which contained 15 statements. The questionnaire used was a Likert scale. Based on the questionnaire, the students preferred to resignation strategy to overcome their anxiety in speaking English. The percentage of resignations was 73%. The second strategy was preparation there were 66%. The third strategy was positive thinking, there were 65%. The fourth strategy was peer seeking, there were 45%. And the lowest strategy was relaxation, there were 33%. The result of the interview showed that the frequent of students’ strategies to overcome anxiety was caused by two factors; unfamiliarity, and attention from others.